Nilai-Nilai Pendidikan Islam Perspektif Ki Hajar Dewantara dalam Tradisi Lokal Selamatan Rumah (Selamatan Bungko) di Dusun Kumalabaru - Aris Ibra Assyauqi; Nur Syarifuddin (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
The Selamatan Bungko tradition in Kumalabaru Hamlet is carried out as a prayer ritual for a newly built house so that it may bring blessings, protection, and comfort to its residents. However, along with the changing times, there have been several modifications in its practice, such as shortening the duration of the burdah recitation and omitting the adhan on one of the house pillars. Using a descriptive qualitative approach with observation and interview methods, this study reveals that the Selamatan Bungko embodies several values: the value of silaturrahmi, which strengthens social relations; the value of mutual assistance, which reflects the spirit of gotong royong (communal cooperation); and the value of exemplarity derived from the recitation of qasidah burdah. Based on Émile Durkheim’s functionalism theory, this tradition also serves as a means of reinforcing social solidarity and internalizing Islamic values in community life.